Sistema unifamiliar de tratamento e reuso de águas cinzas na irrigação de fruteiras em quintais ecológicos - Medeiros, Lana Araújo de (Universidade Federal Rural do Semi-Árido, 2019)
The poor effluents disposal has been causing major environmental and human health problems, since these untreated effluents pollute the water basins and contaminate the soil, causing preventable diseases to the population living in the region. Thinking how to solve this problem, the objective is to design a single-family system for treating and reusing gray water for fruit irrigation in low-cost ecological yards, but which meets some quality specified by tecnical, so that the health of the population and the environment are not harmed. The proposal was developed for implementation in the community Bom Fim, belonging to the municipality of Angicos / RN. In order to make this project possible, it was necessary to know and quantify the effluent generated by the families, to understand the water needs of the plants, to study ANBT norms that would regulate the dimensioning of the materials necessary for the construction of the system and to analyze if its implementation it's viable. After obtaining the necessary understanding by reading the theoretical framework, some analyzes could be performed generating good results, which go beyond the application of the gray water treatment and reuse system, as an improvement in the quality of life of the small farmer considering that he will be better living with drought, better crop development, reduced pollution in water basins. So the small farmer is beneficially using smart water, tackling pollution problems and helping the Northeast and Brazil achieve the United Nations 2030 Agenda Sustainable Development Goals (SDGs) (UN).
Monografia
Keywords: Efluentes; Poluição; Plantas; Qualidade de vida; Effluents; Pollution; Plants; Quality of life; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA